Novel microRNAs modulating ecto-5′-nucleotidase expression - Kordaß, Theresa; Chao, Tsu-Yang; Osen, Wolfram; Eichmüller, Stefan B. (Frontiers in Immunology, 2023)
Introduction: The expression of immune checkpoint molecules (ICMs) by cancer cells is known to counteract tumor-reactive immune responses, thereby promoting tumor immune escape. For example, upregulated expression of ecto-5′-nucleotidase (NT5E), also designated as CD73, increases extracellular levels of immunosuppressive adenosine, which inhibits tumor attack by activated T cells. MicroRNAs (miRNAs) are small non-coding RNAs that regulate gene expression at the post-transcriptional level. Thus, the binding of miRNAs to the 3′-untranslated region of target mRNAs either blocks translation or induces degradation of the targeted mRNA. Cancer cells often exhibit aberrant miRNA expression profiles; hence, tumor-derived miRNAs have been used as biomarkers for early tumor detection. Methods: In this study, we screened a human miRNA library and identified miRNAs affecting the expression of ICMs NT5E, ENTPD1, and CD274 in the human tumor cell lines SK-Mel-28 (melanoma) and MDA-MB-231 (breast cancer). Thereby, a set of potential tumor-suppressor miRNAs that decreased ICM expression in these cell lines was defined. Notably, this study also introduces a group of potential oncogenic miRNAs that cause increased ICM expression and presents the possible underlying mechanisms. The results of high-throughput screening of miRNAs affecting NT5E expression were validated in vitro in 12 cell lines of various tumor entities. Results: As result, miR-1285-5p, miR-155-5p, and miR-3134 were found to be the most potent inhibitors of NT5E expression, while miR-134-3p, miR-6859-3p, miR-6514-3p, and miR-224-3p were identified as miRNAs that strongly enhanced NT5E expression levels. Discussion: The miRNAs identified might have clinical relevance as potential therapeutic agents and biomarkers or therapeutic targets, respectively.